Avaliação do rendimento da extração de pectina da farinha da casca de banana verde tipo cavendish (musa aaa) utilizando um planejamento fatorial - Vasconcelos, Jéssyca Cipriano Barbosa (Universidade Federal do Tocantins, 2020)
In the banana processing chain a large amount of waste with potential for use is generated. Since banana peel is rich in nutrients, one way to reuse it would be to use Cavendish banana peel flour (Musa AAA) to obtain pectin. Therefore, the main objective of this work was the extraction of pectin from the green banana peel flour by the citric acid method and to evaluate its yield using a factorial design. A 2³ factorial design plus three central points were used in which the following independent factors were evaluated: ratio (1:20, 1:12,5 and 1:10); pH (2.0, 2.5 and 3) and extraction time (3, 4 and 5 h). According to the conditions used in pectin extraction, the yield ranged from 5,317 to 17,355% and was close to other authors who worked with the same acid. Planning analysis showed that all factors were significant, with a 95% confidence level. Response surface analysis showed that the best condition for pectin extraction yield from Cavendish banana peel flour was pH 2.0, time 3 hours and 1:20 g / ml ratio. Therefore, the results suggest that Cavendish green banana peel can be reused as it contains a satisfactory pectin content.